Turbulence, Flexibility and Performance of the Long-lived Small Firm - Bernadette Power; Gavin C Reid (Tinbergen Institute, 2003)
This paper focuses on a new concern in the small firm's literature, namely what makes a small firm stay in business for a long time. It reflects a change in economic policy, away from an emphasis on volume of start-ups to an emphasis on quality of start-ups. The basic hypothesis is that flexibility enhances the long run prospects of the small firm. This is explored by examining precipitating causes of organisational change within the small firm, and the consequential adjustments. The study is fieldwork based and uses evidence from face-to-face interviews with 63 owner managers of mature small firms in Scotland. New measures of flexibility and turbulence are used to explain the performance of mature small firms. These depend on our unique body of evidence from interviews with owner managers. Performance is measured using a Likert scale over 28 distinct attributes.Econometric estimates are reported on the relationship between flexibility, turbulence and performance. This is done in two forms. The first involves generalised least squares estimation (with heteroskedastic adjustment) of the relationship between turbulence, four measures of flexibility, and performance. The second involves Heckman sample selection estimation, of this performance relationship. It is found that turbulence has a negative effect on performance. Further, this impact is relatively large. Next in importance are those flexibility factors which can be categorised as precipitating causes of organisational change (as opposed to consequential adjustments) within the mature small firm. Finally, trade-off relationships are found to exist between two of the measures of flexibility (viz. agility and speed). We believe that this trade-off relationship is worthy of further empirical investigation.
Keywords: C42; D21; G33; L2; M13; M21; 330; Flexibility; Firm-Specific Turbulence; Performance; Small Firms.; KMU; Unternehmenserfolg; Organisatorischer Wandel; Schottland; Flexibilität